Highly Sensitive Immunosensing of Carcinoembryonic Antigen Based on Gold Nanoparticles Dotted PB@PANI Core-Shell Nanocubes as a Signal Probe - Dexiang Feng; Lingzhi Chen; Ke Zhang; Shuangshuang Zhu; Meichen Ying; Peng Jiang; Menglan Fu; Yan Wei; Lihua Li (Journal of Analytical Methods in Chemistry)
Herein, a method was developed for the sensitive monitoring of carcinoembryonic antigen (CEA) by gold nanoparticles dotted prussian blue@polyaniline core-shell nanocubes (Au NPs/PB@PANI). First, a facile low-temperature method was used to prepare the uniform PB@PANI core-shell nanocubes with the assistance of PVP, where PB acted as the electron transfer mediator to provide electrochemical signals, and the PANI with excellent conductivity and desirable chemical stability not only played the role of a protective layer to prevent etching of PB in basic media but also effectively improved electron transfer. Importantly, to further enhance the electrical conductivity and biocompatibility of PB@PANI and to further enhance the electrochemical signal and capture a large amount of Ab2, Au NPs were doped on the surface of PB@PANI to form Au NPs/PB@PANI nanocomposites. Subsequently, benefiting from the advantages of core-shell structure nanoprobes and gold-platinum bimetallic nanoflower (AuPt NF), a sandwich-type electrochemical immunosensor for CEA detection was constructed, which provided a wide linear detection range from 1.0 pg·mL−1 to 100.0 ng·mL−1 and a low detection limit of 0.35 pg·mL−1 via DPV (at 3σ). Moreover, it displayed a satisfactory result when the core-shell structure nanoprobe-based immunosensor was applied to determine CEA in real human serum samples.